2014
DOI: 10.1088/1748-9326/9/10/104011
|View full text |Cite
|
Sign up to set email alerts
|

Do US metropolitan core counties have lower scope 1 and 2 CO 2 emissions than less urbanized counties?

Abstract: Recent sustainability research has focused on urban systems given their high share of environmental impacts and potential for centralized impact mitigation. Recent research emphasizes descriptive statistics from place-based case studies to argue for policy action. This limits the potential for general insights and decision support. Here, we implement generalized linear and multiple linear regression analyses to obtain more robust insights on the relationship between urbanization and greenhouse gas (GHG) emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…For reference, US 2016 per capita emissions were roughly 20 metric tons CO 2 e per person (US Census Bureau, 2018b, US Environmental Protection Agency EPA 2018b). The average per capita emissions we found are comparable to the average Scope 1 per capita emissions that Tamayao et al (2014) found for central and outlying counties across US MSAs. Thus, from the perspective of production-based emissions, there appears to be a relationship between the centrality of a county within an MSA and its per capita GHG emissions.…”
Section: 'Under-reported Geographies' Based On Integrated Datasupporting
confidence: 77%
See 3 more Smart Citations
“…For reference, US 2016 per capita emissions were roughly 20 metric tons CO 2 e per person (US Census Bureau, 2018b, US Environmental Protection Agency EPA 2018b). The average per capita emissions we found are comparable to the average Scope 1 per capita emissions that Tamayao et al (2014) found for central and outlying counties across US MSAs. Thus, from the perspective of production-based emissions, there appears to be a relationship between the centrality of a county within an MSA and its per capita GHG emissions.…”
Section: 'Under-reported Geographies' Based On Integrated Datasupporting
confidence: 77%
“…The second part of our analysis focuses on the implications of cities confining their inventories and planning to the city limits. Expanding on the central, outlying, and rural levels of aggregation employed by Tamayao et al (2014), we establish three different geographic categories for evaluating a given metropolitan area: (1) the urban 'core' county/counties, (2) the 'central' counties surrounding the urban core, and (3) the 'outlying' counties of the MSA. For our analysis, we classify the urban 'core' as the county (or counties) that house(s) the primary city of an MSA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, under a productionbased approach, a majority of the electricity sector emissions for that metropolitan area would be attributed to outlying/rural counties in Illinois, Indiana, and Michigan (where the electricity generation facilities are likely located) (see for example Weber et al 2010). A regression-based approach to relate the amount of electricity consumed in a county to the amount of electricity produced in a county has also exhibited a fairly large range of uncertainty (Tamayao et al 2014). By comparing our emission estimates to self-reported estimates produced by cities, our analysis allows for additional comparison between consumption-based and production-based estimates and places any disparities in the context of the overall emissions profile of a metropolitan area.…”
Section: Methodsmentioning
confidence: 99%